Respostas
respondido por:
4
A) ax + ay =
a(x + y)
B) 16x^2 + 20y^2 =
2(8x^2 + 10y^2)
C) 5x + 15^y - 10z =
5(x + 3y - 2z)
D) 4x - 16 =
4(x - 4)
E) Kx + K =
K(x + 1)
F) -5x^3 + 20x^2y^2
-5(x^3 - 4x^2y^2)
Espero ter ajudado!
a(x + y)
B) 16x^2 + 20y^2 =
2(8x^2 + 10y^2)
C) 5x + 15^y - 10z =
5(x + 3y - 2z)
D) 4x - 16 =
4(x - 4)
E) Kx + K =
K(x + 1)
F) -5x^3 + 20x^2y^2
-5(x^3 - 4x^2y^2)
Espero ter ajudado!
anabeatrizlima14:
Obrigado você me ajudou muito
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás